Pattern layout optimization for low series resistance and capacitance in gan schottky barrier diodes - Ahmad Syahiman, Mohd Shah (2012)
Rectenna, which stands for rectifying antenna, is used to capture and convert the microwave power to the direct current. Applications of the rectenna are mainly focused between remote areas, where the physical power connections are not feasible for transferring power [29]. In this rectenna system, one of the important elements, is Schottky barrier diode. This diode plays as a rectifier. This diode has to possess the following characteristics, such as low series resistance,R5 , low zero-biased junction capacitance, Co, low turn-on voltage, VON, and high breakdown voltage, VBR in order to obtain a higher efficiency of power conversion [1]. However, the commercially-available Si and GaAs-based diodes have suffered from their low breakdown voltage which consequently,allows them to be applicable only for .low power transmission system. Thus, GaN is one of the candidates to replace these two materials due to its high breakdown voltage [4]. In this study, we introduced an Ultra-finger diode as this structure owned a longer Schottky perimeter. From this study,the trade-off relation between and series resistance and capacitance was revealed as the series resistance significantly decreased by expanding the perimeter of the Schottky contacts even at the similar Schottky area. This ultra-finger diode exhibited lower time constant, 'r value than the conventional circular diode.The value of time constant is minimized by maximizing the value of Schottky perimeter multiplied with the area.From this investigation, we propose the ultra-finger diode as an alternative solution for better optimization for low series resistance and capacitance.